Growth Performance and Physiological Responses of Garut Lambs Fed Diets Mung Bean Sprout Waste at Different Times - Rahayu, Sri; Yamin, Mohamad; Sumantri, Cece; Astuti, Dewi Apri (Pakistan Journal of Nutrition, 2015)
This study evaluated the effect of a diet containing mung bean sprout waste (MBSW) as a fiber source and feeding time on the growth performance and physiological responses of Garut lambs. Feeding regimens generated by a factorial randomized block design with two factors- diet and feeding time-were assigned to twenty Garut male lambs aged 6-7 months (BW 15.42±2.42 kg). The two diets (D) formulated with a dry matter (DM) base were D1 (60% concentrate 1+40% natural grass) and D2 (60% concentrate 2+40% MBSW). Feeding times were in the morning (MF, 6:00-7:00 am) or the evening (EF, 5:00-6:00 pm). The animals were reared in individual cages and fed with 5% DM/kg body weight/day. Nutrient intake (DM, crude protein (CP), total digestible nutrient (TDN) and average daily gain (ADG) of lambs fed D2 was significantly (p